Optimum Seeding Rate for Different Wheat Varieties in Kansas - R. Lollato; G. Cramer; A. K. Fritz; G. Zhang (Kansas Agricultural Experiment Station Research Reports, 2017)
Seeding rate is an important management practice affecting wheat yield. Wheat varieties differ in their tillering capacity and therefore in their yield response to seeding rate. Our objectives were to evaluate the tillering and yield response of different modern wheat varieties to seeding rate. The study was conducted in Hutchinson and Manhattan, KS, during the 2015-16 growing season. Seven wheat varieties (Everest, KanMark, 1863, Joe, Tatanka, Larry, and Zenda) were sown at five different seeding rates (0.6, 0.95, 1.3, 1.65, and 2 million seeds per acre). Tiller number and grain yield were measured in the spring. Increasing plant population decreased the number of spring tillers sustained by the different varieties from more than eight tillers per plant at 600,000 seeds per acre to fewer than four tillers per plant at 2 million seeds per acre. There were varietal differences in tillers per plant, with the variety Joe standing out as a high-tillering variety. At both locations, wheat grain yield increased with increased seeding rates and was maximized at approximately 0.8-0.95 million emerged plants per acre. Further increases in seeding rate did not affect grain yield.
Keywords: Wheat; seeding rate; variety